Andrographolide inhibits proliferation and induces cell cycle arrest and apoptosis in human melanoma cells - Liu, Guo (Oncol Lett, 2018)
Andrographolide (Andro), a natural compound isolated from Andrographis paniculata, has been demonstrated to have anticancer efficacy in several types of tumors. In the present study, the anticancer effects and mechanism of Andro in human malignant melanoma were investigated. Cell viability analysis was performed using an MTT assay and the effect of Andro on the cell cycle and apoptosis of human malignant melanoma cells was determined by flow cytometry. Western blot analysis was performed to evaluate the protein expression levels of human malignant melanoma cells following treatment with Andro. The results revealed that Andro potently inhibited cell proliferation by inducing G2/M cell-cycle arrest in human malignant melanoma C8161 and A375 cell lines. In addition, treatment with Andro induced apoptosis, which was associated with the cleavage of poly(adenosine diphosphate-ribose) polymerase and activation of caspase-3. It was observed that Andro induced activation of the c-Jun N-terminal kinase and p38 signaling pathway, which may be connected with cell cycle arrest and apoptosis. In conclusion, the results demonstrated that Andro may be a promising and effective agent for antitumor therapy against human malignant melanoma.